2018
DOI: 10.1371/journal.pone.0191241
|View full text |Cite
|
Sign up to set email alerts
|

A portable prototype magnetometer to differentiate ischemic and non-ischemic heart disease in patients with chest pain

Abstract: BackgroundMagnetocardiography (MCG) is a non-invasive technique used to measure and map cardiac magnetic fields. We describe the predictive performance of a portable prototype magnetometer designed for use in acute and routine clinical settings. We assessed the predictive ability of the measurements derived from the magnetometer for the ruling-out of healthy subjects and patients whose chest pain has a non-ischemic origin from those with ischemic heart disease (IHD).MethodsMCG data were analyzed from a technic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…Since costs and operational difficulty related to mandatory need of heavy electromagnetic shielding and cryogenic instrumentations has significantly impaired the clinical application of the MCG, the present trend is toward the development of novel non‐cryogenic recording systems to perform MCG at the patient’s bedside with mobile unshielded instruments (Ghasemi‐Roudsari et al, ; Mooney et al, ). However, clinical experience with MCG of AF patients performed in unshielded hospital environments was very limited, so far (Fenici & Brisinda, , ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since costs and operational difficulty related to mandatory need of heavy electromagnetic shielding and cryogenic instrumentations has significantly impaired the clinical application of the MCG, the present trend is toward the development of novel non‐cryogenic recording systems to perform MCG at the patient’s bedside with mobile unshielded instruments (Ghasemi‐Roudsari et al, ; Mooney et al, ). However, clinical experience with MCG of AF patients performed in unshielded hospital environments was very limited, so far (Fenici & Brisinda, , ).…”
Section: Discussionmentioning
confidence: 99%
“…All previous MCG studies were carried out in magnetically shielded rooms, providing optimal signal‐to‐noise ratio but, beside costs, not practical for routine ambulatory clinical application of the method. Since the present trend instead is toward the development of mobile non‐cryogenic instrumentations to carry unshielded MCG at patient bedside (Ghasemi‐Roudsari et al, ; Mooney et al, ), this retrospective study aimed to preliminarily assess the accuracy of ambulatory atrial MCG, recorded in an unshielded hospital laboratory for interventional electrophysiology, to predict PAF events, using parameters derived from automatic analysis of atrial magnetic field (MF) dynamics and of the three‐dimensional (3D) spatial dynamics of the atrial electromagnetic vector (EMV) calculated after solution of the inverse problem with the Effective Magnetic Dipole (EMD) model. Our hypotheses were that reliable MCG of atrial activity is feasible also in unshielded hospital ambulatory with a sensitivity adequate for clinical quantitative assessment of markers of AF vulnerability.…”
Section: Introductionmentioning
confidence: 99%
“…It is capable of recording heart vortex currents, which are undetectable by ECG 79,85 . Clinical studies have investigated MCG for the identification of patients with ACS even in the absence of specific findings on ECG and positive marker tests 81,86–91 . A retrospective study demonstrated that specific parameters could differentiate NSTEMI patients from age‐matched controls (patients who experience chest pain but do not have MI) with 81% accuracy.…”
Section: Diagnostic and Predictive Value Of Emf‐based Modalitiesmentioning
confidence: 99%
“…These magnetometers need to be operated in a magnetically shielded room to avoid background noise 79 . Various types of MCG devices have been developed today, such as SQUID magnetocardiography in an unshielded environment, laser‐pumped optical magnetometers, and portable miniaturized induction coils 80,81 . During the past 30 years, researchers have conducted extensive studies to evaluate the diagnostic and predictive ability of MCG for coronary artery disease (CAD) and arrhythmic events 9,82,83 .…”
Section: Diagnostic and Predictive Value Of Emf‐based Modalitiesmentioning
confidence: 99%
“…[12] Evaluation of the device in 70 patients with ischaemic heart disease, 69 controls and 37 healthy volunteers showed that a logistic regression model based on MCG predictors could differentiate patients from controls with a specificity of 35.0%, sensitivity of 95.4%, and negative predictive value of 97.8% (area under the curve 0.78). [13] This suggested potential for the portable MCG to have a role in ruling out ACS, but further research was required to derive an algorithm for the MCG to diagnose ACS, determine the threshold used to indicate a positive test and then validate the algorithm and threshold in a separate cohort. The MCG measures a number of parameters that can be combined in an algorithm to predict the probability of ACS.…”
Section: Introductionmentioning
confidence: 99%